Benedicte Nielsen Whitehead, Thomas Olander, Birgit Anette Olsen, Jens Elmegård Rasmussen (eds.), The Sound of Indo-European: Phonetics, phonemics, and morphophonemics - Villanueva Svensson, Miguel (Baltistica, 2013)
–
Keywords: The Sound of Indo-European﻿; historical phonology; phonetics; phonemics; morphophonemics